Hydrogen Embrittlement Susceptibility of Ca-Treated Linepipe Steel Skelp - Filice, Sara (My University, 2018)
The aim of this research is to identify problematic microstructural features as hydrogen traps in linepipe steel that serve to increase the hydrogen embrittlement susceptibility. A comparison is made between the hydrogen trapping capacity and associated hydrogen embrittlement susceptibility of Ca-treated X60 grade steel skelp and X70 grade steel skelp: the latter typically being more susceptible to hydrogen-induced cracking in sour environments. Through-thickness variations in the steel skelp microstructure were characterized across multi-length scales using light optical microscopy (LOM) and scanning electron microscopy (SEM) equipped with X-ray energy dispersive spectroscopy (EDS). Key features under study include the composition, shape, and distribution of non-metallic inclusions, as well as differences in features present between the quarterline (¼ and ¾ depths) and centerline (½ depth) microstructures. The type, count, and average size of inclusions present in both steel skelp grades were analyzed using an automated SEM-EDS technique called ASPEX®. Major types of inclusions detected in both grades of steel skelp include those containing Ca, Al, Mn, Mg and Ti as major elements. Overall, the area fraction of inclusions detected in the X70 steel was larger than those detected in the X60 with the exception of Ti-containing inclusions, which had a larger area fraction within the X60 steel. Comparing the number of detected inclusions shows that there was overall slightly less Ca-containing inclusions and significantly less Ti-containing inclusions detected in the X70 steel but there was generally more Al-containing, Mg-containing, and Mn-containing inclusions than those detected in the X60 steel. Thermal desorption spectroscopy (TDS) measurements were made on samples prepared from the ¼, ½, and ¾ depths of X60 and X70 steel skelps after galvanostatic cathodic charging in an As2O3-containing solution using an applied current density of −10 mA/cm2. Hydrogen release was measured using a HYDROSEEL® probe while the sample was heated from 20°C to 650°C to detect temperature values at which hydrogen gas release peaks occurred, and thus provide information on types of reversible and/or irreversible traps present. The TDS results suggests that non-metallic inclusions indeed serve as irreversible traps along with grain boundaries and dislocations, which serve as reversible traps. Hydrogen permeation measurements were also made on samples prepared from the ¼, ½, and ¾ depths after galvanostatic cathodic charging in an As2O3-containing solution using an applied current density of −10 mA/cm2. Hydrogen gas release was measured using a HYDROSEEL® probe while the sample remained at room temperature (~20°C), providing information regarding the potency of reversible hydrogen traps when subjected to a flux of hydrogen. Only reversible traps can be detected at room temperatures due to their low binding energies. Higher temperatures are required to overcome the larger binding energies associated with irreversible traps. The hydrogen permeation results indicate no significant effect of through-thickness variations in the X60 steel, but the centreline depth of the X70 steel skelp trapped a larger quantity of hydrogen than either of the two quarterline depths, indicating the presence of a distinct problematic trap. The X70 steel skelp was also observed to trap more hydrogen than the X60 steel skelp. The observed hydrogen trapping capacity was linked to the hydrogen embrittlement susceptibility by comparing the uniaxial tensile behaviour of centreline samples with and without hydrogen charging applied as a pre-treatment step. Hydrogen charging was achieved by galvanostatic cathodic polarization at an applied current density of −10 mA/cm2 for 24 h in an NH4SCN-containing solution while simultaneously loading the samples to 85% of the yield strength using a proof ring tensile test cell. An increase in hydrogen embrittlement as a result of pre-charging was confirmed through tensile plots by comparing the area of reduction and failure strain of charged samples to uncharged samples. A decrease in both values was observed in the charged samples indicating a loss in ductility as a result of hydrogen charging. Fracture surfaces were imaged using SEM and inclusions of interest were analyzed for elemental composition using EDS. Inclusions observed along the fracture surfaces include oxysulfides of Ca and Al, oxides of Mg, Al-Ca-Si oxides, and Al2O3-containing inclusions which are likely to be heterogeneous Al-Ca-O inclusions.
Hydrogen Embrittlement Susceptibility of Linepipe Steel
Keywords: Hydrogen Embrittlement; Hydrogen Trapping; Pipeline Steel